Vortech recliner / Muhd Hadif Hafiy Samsul Fikri ... [et al.] - Samsul Fikri, Muhd Hadif Hafiy; Muhammad Razif, Nur Shaheera; Alfiasa, Al-Qurratu'aini; Ammar, Saifullah (2024)
In this project, our paramount goal is to meticulously craft furniture that not only grants users a sanctuary of comfort for unwinding in recreational settings but also champions the cause of environmental sustainability. Harnessing the timeless allure and ecological virtues of wood as our primary material, we intertwine its natural elegance with the seamless integration of state-of-the-art technology, attuned to the pulse of contemporary trends. Through the discerning selection of technologically advanced materials imbued with eco-conscious principles, we navigate the delicate balance between modernity and ecological stewardship, ensuring that each piece of furniture serves as a testament to our commitment to safeguarding the planet's future. As a result, every meticulously designed furniture ensemble harmonizes the rustic charm of wood with the innovative edge of technology, fostering environmental sustainability while enveloping users in a realm of aesthetic allure and unparalleled comfort.